Effect of a second metal (Co, Cu, Mn or Zr) on nickel catalysts derived from hydrotalcites for the carbon dioxide reforming of methane. Issue 74 (25th July 2016) - Yu, Xiaopeng; Zhang, Fubao; Chu, Wei
Abstract : NiCo and NiCu catalysts exhibited enhanced stability compared with a Ni catalyst for the dry reforming of methane. On the contrary, NiMn and NiZr catalysts decreased the reforming stability. Abstract : Additive (Co, Cu, Mn or Zr)-promoted Ni catalysts derived from hydrotalcites were prepared by co-precipitation for the carbon dioxide reforming of methane. XRD, SEM-EDS, H2 -TPR, XPS, TG-DTG, TEM, N2 physisorption and H2 -chemisorption were used to investigate the structure and the deactivation characteristics of the catalysts. All the catalysts exhibited the formation of Mg(Ni, Al)O periclase with a mesoporous structure. The initial activity of the catalysts decreased in the sequence: NiCo > Ni > NiCu > NiMn > NiZr. The NiCo catalyst exhibited the highest catalytic activity due to its enhanced metal dispersion and increased active-metal content. However, the decoration of Ni clusters with Mn2 O3 and ZrO2 species on the NiMn and NiZr catalysts retarded the accessibility of Ni-active centres, thereby reducing their initial catalytic activity. Compared to the Ni catalyst, the NiCu catalyst improved significantly the reforming stability because of the formation of the NiCu alloy and the lower rate of coke deposition. The superior reforming stability of the NiCo catalyst resulted from its strong resistance to carbon deposition and improved metal-sintering resistance. The NiCo catalyst effectively inhibited coking, which could be associated with its small metal size and its high metal dispersion. The decreased stability was observed for the NiMn and NiZr catalysts owing to their increased rate of coke deposition and the formation of carbon filaments.